Replication error phenotype, clinicopathological variables, and patient outcome in Dukes' B stage II (T3, N0, M0) colorectal cancer. Issue 2 (1st February 2000) - Curran, B; Lenehan, K; Mulcahy, H; Tighe, O; Bennett, M A; Kay, E W; O'Donoghue, D P; Leader, M; Croke, D T
Abstract : AIMS: To examine the relation between the replication error (RER) phenotype and other genetic events, clinical features, and long term survival in patients with Dukes' B stage II (T3, N0, M0) colorectal cancer. METHODS: RER phenotype was investigated in 159 patients by PCR amplification of microsatellite marker loci on chromosomes 5q, 17p, 17q, and 18q from tumour DNA extracted from archival tissue. Data on activating c-Ki- ras mutations were available from a previous study. Immunohistochemical detection of p53 and c-erbB-2 expression was performed on paraffin wax embedded tissue. RESULTS: Of 159 colorectal cancers studied, 22 (14%) were RER+ while 137 (86%) were RER− for two or more loci. RER+ tumours were more commonly located in the right colon, tended to be larger than RER− tumours, and were more often poorly differentiated than RER− cancers. No significant associations were seen between RER status and the presence of a mutant c-Ki- ras gene, or between RER status and p53, c-erbB-2, or c-myc gene expression. Univariate survival analysis showed that outcome was similar in RER+ and RER− cases. Multivariate survival analysis showed that the relative risk of death for patients with RER+ cancers was 0.95 that of patients with RER− cancers. CONCLUSIONS: The results suggest that, while the RER phenotype may be associated with some differences in tumour pathology (site, size, differentiation), it is not associated with the genetic alterations studied or with significant differences in long term survival.